2020
DOI: 10.1007/s11764-020-00929-0
|View full text |Cite
|
Sign up to set email alerts
|

Health outcomes in offspring born to survivors of childhood cancers following assisted reproductive technologies

Abstract: Purpose An increasing number of childhood cancer survivors are using assisted reproductive technologies (ART) to overcome treatment-related fertility impairment. We report perinatal and health outcomes of offspring born to survivors following ART. Methods The FeCt Multicenter Offspring Study surveyed the health of offspring of childhood cancer survivors. Health outcomes in offspring born to survivors following ART (n = 57, 4.6%) or after spontaneous conception (n = 1182) were assessed in the German cohort (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Survivors of childhood cancer are at increased risk for fertility impairment, and thus, numbers of ART utilisation in this cohort have increased in recent years. In a previous study, ART was used by twice as many survivors as in the general population [ 30 ]. Our current analyses revealed that childhood cancer survivors also requested ART more often (4.5%) than their siblings (3.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Survivors of childhood cancer are at increased risk for fertility impairment, and thus, numbers of ART utilisation in this cohort have increased in recent years. In a previous study, ART was used by twice as many survivors as in the general population [ 30 ]. Our current analyses revealed that childhood cancer survivors also requested ART more often (4.5%) than their siblings (3.7%).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms, including epigenetic changes that may occur during preimplantation and the development of uterine reprogramming, are currently under debate [ 28 , 29 ]. Publications examining ART and health issues of childhood cancer survivor offspring are rare [ 30 ]. Our study compared: (i) the prevalence of ART utilisation in survivors and their siblings, (ii) perinatal outcomes, malformations, heart defects and cancer in ART-conceived survivor offspring with those conceived spontaneously and (iii) the outcomes of survivor offspring vs. sibling offspring.…”
Section: Introductionmentioning
confidence: 99%
“…There were more multiples born and a higher prevalence for low birth weight in the offspring of cancer survivors, whereas the prevalence for preterm birth or small for gestational age were comparable to spontaneously conceived offspring of cancer survivors. Neither childhood cancer nor congenital malformations were found to be increased in the offspring (1). Therefore, it is extraordinarily important that every patient of reproductive age and every child should have the possibility to be counseled in a specialized center by gynecologists, reproductive/ endocrine specialists, or urologists/andrologists before the gonadotoxic treatment starts as recommended by the current S2k guideline on fertility preservation for patients with malignant diseases (2).…”
Section: Childhood Cancer and Infertilitymentioning
confidence: 99%
“…These data are consistent with our findings. In contrast, a study on cancer survivors’ offspring conducted by a German group on 1239 women found that their health status was comparable with that of the general population [ 15 ].…”
Section: Fertility Counseling In Childhood and Adolescent Cancer Survivorsmentioning
confidence: 99%